Roles of Embryonic Lethal Abnormal Vision-Like RNA Binding Proteins in Cancer and Beyond - Cai, Haijian; Zheng, Dandan; Yao, Yizhu; Yang, Lehe; Huang, Xiaoying; Wang, Liangxing (Frontiers in Cell and Developmental Biology, 2022)
Embryonic lethal abnormal vision-like (ELAVL) proteins are RNA binding proteins that were originally discovered as indispensable regulators of the development and functioning of the nervous system. Subsequent studies have shown that ELAVL proteins not only exist in the nervous system, but also have regulatory effects in other tissues. ELAVL proteins have attracted attention as potential therapeutic targets because they stabilize multiple mRNAs by binding within the 3'-untranslated region and thus promote the development of tumors, including hepatocellular carcinoma, pancreatic cancer, ovarian cancer, breast cancer, and colorectal carcinoma. Previous studies have focused on these important relationships with downstream mRNAs, but emerging studies suggest that ELAVL proteins also interact with non-coding RNAs. In this review, we will summarize the relationship of the ELAVL protein family with mRNA and non-coding RNA and the roles of ELAVL protein family members in a variety of physiological and pathological processes.